Effect of EM1 Bio stimulants in some chemical and physics characteristics of Plum Varieties (Prunus salicina L.) (Journal of Hama University, 2019)
The aim of this research is to study effect of foliar and soil fertilization by EM1 on physical and quality fruit of plum Tree var "Beauty , Santa Rosa  " The application of fertilization by EM1 concentrates (2-4-6 ml/L both foliar and soil) during seasons of 2017 in the following dates: ( stage bud-break, after fruit set, month before fruit harvest). The Effective Microorganisms EM1 treatment led to improvement ripe fruits quality two varieties comparing with the control. The best treatment was which had the fertilization adding by EM1 in concentration of (6 ml/L),which reached high average of weight and length  at Beauty variety (49.73 g - 4.33 cm) in the foliar (49.63 g -4.33 cm) in the soil comparing with the control (43.46 g - 4.10 cm) , while at  Santa Rosa variety (44,36 g - 4.83 cm) in the foliar (43.96 g - 4.16 cm) in the soil comparing with the control (33.21 g-3.70 cm) .The concentrations of  (6 ml/L) of Effective Microorganisms (EM1) had good improvement in chemical characters of fruit both variety. That increase the content of T.S.S (13.87-12.76 % soil ) , (12.29-11.64 % foliar )  and T.S (6.02-5.47 % soil ) , (5.67-5.04 % foliar ) and vitamin C (43.13-32.19 mg foliar) , (30.19-30.19 mg soil ) in order to both variety comparing with the least of value in the control . Foliar fertilization had superiority on soil fertilization in rising in concentration were increased of macro elements in the ripe fruits . The concentrations of these characters were higher in the Beauty variety which superior to Santa Rosa .